Методологічні основи проєктування п’єзоелектричних активаторів дворежимних струминних апаратів - Рябовол, Антон Вадимович; Riabovol, Anton (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Мета дослідження полягає у визначенні методичних засад проєктування п’єзоелектричних активаторів дворежимних струминних апаратів на основі аналізу їх функціональних принципів, конструктивних параметрів і режимів роботи. Наукова новизна полягає у формуванні узагальненої чисельної моделі процесу формування струменя з урахуванням квазістатичного й динамічного режимів та у визначенні системи критеріїв ефективності активатора. Практична цінність дослідження зумовлена можливістю використання отриманих рекомендацій для параметризації й налаштування активаторів у струминних апаратах. Основними результатами є встановлення залежностей між електричними параметрами, механічною реакцією п’єзоперетворювача та динамікою формування струменя, а також виявлення умов, що мінімізують утрати енергетичної ефективності за перемикання режимів. Висновки підтверджують доцільність застосування принципів адаптивної оптимізації для забезпечення стабільного дворежимного функціонування й підвищення продуктивності струминних апаратів. /// EN: A comprehensive analysis of modern approaches to the design of piezoelectric actuators for dual-mode jet devices is carried out, covering the functional principles of converting electrical energy into mechanical excitation, the structural features of piezoelectric transducers, and the classification of jet-forming regimes in devices with piezoelectric control. The differences between static and dynamic operating modes are detailed, particularly regarding their areas of application, requirements for the electrical parameters of the actuator, and the types of deformation transmitted to the jet channel. It is shown that a key prerequisite for synthesizing an effective actuator is the consistency of the mathematical models describing the interaction between the piezoelectric element and the internal hydrodynamic environment of the jet channel, as well as the consideration of the frequency characteristics of the piezoelectric transducer that determine the response speed to the control signal. The parameters of the mechanical response of the piezoelectric actuator affecting the dynamics of jet formation – including the waveform of the applied voltage, the disturbance amplitude, the geometric dimensions of the transducer, and the physical–mechanical properties of the working medium – are generalized. A generalized numerical model of the jet formation process is presented, which makes it possible to evaluate the influence of piezo-excitation in both quasi-static and dynamic operating modes. A comparative analysis of jet-forming regimes is performed, and the switching limits of the piezoelectric transducer are determined – ensuring minimization of energy efficiency losses and improving the stability of the jet device when switching between operating modes. The influence of design parameters of the actuator on the amplitude and shape of the flow is analyzed, which makes it possible to formulate general recommendations for achieving stable dual-mode operation over a wide range of working frequencies. Based on the obtained relations, a system of criteria for evaluating the effectiveness of the piezoelectric actuator is formulated, including jet intensity and stability, response speed to the control signal, consistency of mechanical loading with the electrical characteristics of the actuator, and the resistance of the jet formation process to changes in external conditions. Practical recommendations are substantiated for the parameterization and tuning of piezoelectric actuators based on the principle of adaptive optimization, which makes it possible to increase the dynamic performance of jet devices and ensure their stable operation.
Methodological foundations for designing piezoelectric actuators of dual-mode jet devices
Keywords: п’єзоелектричний активатор; дворежимний струминний апарат; математичне моделюван- ня; формування струменя; динамічний режим; критерії ефективності; синтез активатора; piezoelectric actuator; dual-mode jet device; mathematical modeling; jet formation; dynamic mode; performance criteria; actuator synthesis